Performance of Syariah Regional Development Banks in Indonesia: Maqashid Syariah Approach - Maulana, Nafiz; Hamzani, Umiaty (LifeSciFi, 2025)
Islamic banking in Indonesia continues to grow, yet its performance evaluation often overlooks the broader ethical and social objectives of Sharia principles. This study employs the Sharia Maqashid Index (SMI) and the Sharia Conformity and Profitability (SCnP) frameworks to evaluate the performance of Indonesia’s Islamic Regional Development Banks (BPD Syariah) from 2020 to 2024. It assesses both their adherence to sharia principles and their financial outcomes. Using a quantitative descriptive approach, the research analyzes secondary data drawn from the annual financial reports of BPD Syariah institutions. Findings indicate a positive relationship between the SMI and financial performance. For instance, Bank NTB Syariah and Bank Aceh Syariah demonstrate high levels of sharia compliance and strong profitability. In contrast, banks such as Bank Sumut and Bank Nagari, which show lower levels of sharia conformity, tend to be less profitable. These results highlight the importance of aligning sharia compliance with financial performance to ensure the long-term viability of Islamic banking. The study contributes to existing literature by integrating sharia compliance into financial performance evaluations of Islamic banks. It underscores the necessity of embedding Sharia governance and ethical banking practices into the core business strategies of BPD Syariah in Indonesia.